Spatial integration of maize markets in post-liberalized Uganda - Rashid, Shahidur (International Food Policy Research Institute, 2004)
Using weekly price data for two sub-periods, this paper analyzes how Ugandan maize market performed in the years following agricultural market liberalization in the early 1990's. For each time period, the extent of integration, causality among spatial locations, and relative importance of spatial locations in price formation are examined. The extent of integration, defined as a set of markets that shares common long-run price information, and the causal relationships among markets have been tested within Johansen's cointegration framework. The relative importance of each market locations is examined by estimating the common trend coefficients with a dynamic vector moving average model. Results indicate that, while there has been an overall improvement in spatial price responsiveness, the northern districts, which have been in a state of insurgency since 1986, continue to lack integration with major consumption markets in the central region. Causality test results show that compared to the 1993-1994-time period, representing the early years of liberalization, interdependence among markets has increased. Estimates of the common integrating trend suggest that public policies, such as price stabilization, can have desired impacts by targeting a small number of locations. These results are consistent with recently conducted household and market surveys in the country.